Pediatric Osteochondral Lesions - Abdullah, Selwan B.; Iyer, Ramesh S.; Shet, Narendra S. (Seminars in Musculoskeletal Radiology, 2018)
Osteochondral lesions are common in children and may arise from a variety of etiologies. Although they most frequently occur in the knee, other joints may be involved including the ankle and elbow. We describe the typical imaging appearance of osteochondral lesions with a focus on radiographs and magnetic resonance imaging. Assessment of the stability of these lesions is of paramount importance in directing management. As such, we describe staging schemes as well as imaging features differentiating stable from unstable lesions. Finally, we briefly discuss management strategies as they correlate to imaging findings.
Keywords: pediatric; bone lesions; osteochondral lesions; magnetic resonance imaging; osteochondral defects